A Bibliometric Analysis of Force Concept Inventory Research in Physics Education: Trends, Contributors, and Research Focus - Nabila Maulida; Nurlina Nurlina (Universitas Lambung Mangkurat, 2026)
The Force Concept Inventory (FCI) has become a cornerstone in physics education research; however, a comprehensive mapping of its global research landscape remains limited. This study addresses this gap through a bibliometric analysis of FCI-related publications indexed in Scopus from 2006 to 2025 (N = 308). The analysis combines performance analysis (publication trends, citation impact, and contributions of authors, institutions, and countries) with science mapping using VOSviewer to examine collaboration networks and keyword co-occurrence. The results indicate a fluctuating yet overall increasing publication trend, with a peak in 2019. Research productivity and influence are dominated by authors and institutions from the United States, which also serves as the central hub of international collaboration. Keyword analysis reveals that FCI research primarily focuses on evaluating instructional interventions, followed by misconceptions, psychometric analysis, gender equity, and emerging themes such as learning analytics and technology-enhanced assessment. These findings demonstrate that the role of FCI has evolved from a tool for measuring learning gains into a rich data source for cognitive and data-driven analysis in physics education. This study provides a structured overview of the field and highlights the need to strengthen global collaboration and integrate advanced analytical approaches.